Institutionalized child care experiences: the hidden side of work - Ruth Irmgard Bärtschi Gabatz; Eda Schwartz; Viviane Marten Milbrath
Abstract Objective: To know the caregiver's perception about the work/care with the institutionalized child. Methods: Qualitative research that used the Theory of Attachment and Symbolic Interactionism as theoretical references and the Grounded Theory as a methodological reference. Data was collected through semi-structured interviews with 15 caregivers of a child sheltering institution, in the year 2015. The analysis was performed from the open coding and categorization. Results: Care work aims to meet the needs of institutionalized children, focusing on food, hygiene and education. In addition, it is little recognized, which generates a feeling of devaluation in caregivers. Conclusions: Continued qualification and support to the caregivers is indispensable for elaborating more effective and integral work/care strategies.